Gastroesophageal reflux related changes after sleeve gastrectomy and sleeve gastrectomy with fundoplication: A retrospective single center study - Aili, Aikebaier; Maimaitiming, Maimaitiaili; Maimaitiyusufu, Pierdiwasi; Tusuntuoheti, Yusujiang; Li, Xin; Cui, Jianyu; Abudureyimu, Kelimu (Frontiers in Endocrinology, 2022)
Background: The worsening of gastroesophageal reflux disease (GERD) and “de novo” GERD after laparoscopic sleeve gastrectomy (LSG) is a major concern as it affects the patient’s quality of life; the incidence of GERD after LSG is up to 35%. Laparoscopic sleeve gastrectomy with fundoplication (LSGFD) is a new procedure which is considered to be better for patients with morbid obesity and GERD, but there is a lack of objective evidence to support this statement. Methods: Fifty-six patients who were classified as obese underwent surgery from January 2018 to January 2020. Patients who were obese and did not have GERD underwent LSG and patients who were obese and did have GERD underwent LSFGD. The minimum follow-up time was 22 months and there were 11 cases lost during the follow-up period. We analyzed the short-term complications and medium-term results in terms of weight loss, incidence of de novo GERD/resolution of GERD, and remission of co-morbidities with follow-up. Results: A total of 45 patients completed the follow-up and a questionnaire-based evaluation (GERD-Q), of whom 23 patients underwent LSG and 22 patients underwent LSGFD. We had 1 case of leak after LSGFD.No medium or long- term complications. The incidence of de novo GERD after LSG was 52.2% at the 12 month follow-up and 30.4% at the mean 34 (22–48) month follow-up. The remission of reflux symptoms, for patients who underwent LSGFD, was seen in 19 (86.4%) of 22 patients at 12 months and 20 (90.1%) of 22 patients at the mean 34 (22-48) month follow-up. The two groups did not have any significant difference in the effect of weight reduction and comorbidity resolution. Conclusion: The incidence of de novo GERD after LSG is high,LSG resulted in the same weight loss and comorbidity resolution as LSGFD，in patients who are morbidly obese and experience GERD, and LFDSG prevent the occurrence and development of GERD，combination of LSG with fundoplication (LSGFD) is a feasible and safe procedure with good postoperative results,which worthy of further clinical application.